2020
DOI: 10.1016/j.asmr.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Statistical Shape Modeling in Quantifying Femoral Morphologic Differences Between Symptomatic and Nonsymptomatic Hips in Patients with Unilateral Femoroacetabular Impingement Syndrome

Abstract: To determine whether statistical shape modeling can detect subtle morphologic differences in the shape of the proximal femur that correlate with clinical findings of unilateral femoroacetabular impingement syndrome. Methods: Patients who had diagnoses of unilateral femoroacetabular impingement syndrome and who had existing computed tomography scans of their pelvises were included. Three-dimensional shape models in the form of triangle meshes were generated from the computed tomography images. Statistical shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Currently, for the diagnosis and quantification of cam‐­type morphology, the field mainly relies on two­‐dimensional (2D) radiographs. Since abnormal bony morphology clearly constitutes a three­‐dimensional (3D) problem, the clinical use of radiographs as screening modality still represents a significant barrier for the morphological evaluation, despite new techniques have been proposed to three­‐dimensionally approach cam‐­type FAIS resections 5–15 . The consequence of inadequate 3D morphologic assessment is potential incomplete resection of the proximal femur to address cam‐­type FAIS, which has been cited as the primary reason for revision surgery 16–20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, for the diagnosis and quantification of cam‐­type morphology, the field mainly relies on two­‐dimensional (2D) radiographs. Since abnormal bony morphology clearly constitutes a three­‐dimensional (3D) problem, the clinical use of radiographs as screening modality still represents a significant barrier for the morphological evaluation, despite new techniques have been proposed to three­‐dimensionally approach cam‐­type FAIS resections 5–15 . The consequence of inadequate 3D morphologic assessment is potential incomplete resection of the proximal femur to address cam‐­type FAIS, which has been cited as the primary reason for revision surgery 16–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Since abnormal bony morphology clearly constitutes a three-dimensional (3D) problem, the clinical use of radiographs as screening modality still represents a significant barrier for the morphological evaluation, despite new techniques have been proposed to three-dimensionally approach cam-type FAIS resections. [5][6][7][8][9][10][11][12][13][14][15] The consequence of inadequate 3D morphologic assessment is potential incomplete resection of the proximal femur to address cam-type FAIS, which has been cited as the primary reason for revision surgery. [16][17][18][19][20] The current clinical approach for the quantification of proximal femur bony morphology also exposes patients to ionizing radiation, in cases of both radiographs and computed tomography (CT).…”
mentioning
confidence: 99%
“…Traditional registration methods use ICP (Iterative Closest Point) algorithm [17], [18]. This method achieves registration by minimizing the distance between the two models.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] There is considerable variation in three-dimensional (3D) hip joint bone shape among individuals, which leads to the challenge of differentiating between abnormal bone shape and normal anatomic structural variation. 12,[16][17][18][19][20][21][22] The primary method for evaluating the 3D shape of the femur in people with suspected FAIS is through measure of the alpha angle on standard radiographs. 23,24 However, this two-dimensional (2D) planar approach provides little information on the exact location and extent of the cam deformity, thereby representing a considerable limitation in understanding the role this morphology plays in the development of cam-type FAIS.…”
mentioning
confidence: 99%
“…25,26 A number of studies have tried to incorporate 3D patientspecific analyses in the diagnosis and surgical planning for FAIS. [17][18][19][20][34][35][36][37][38] Wong et al 35 found that a preoperative evaluation of a computerized tomography (CT)-based 3D printed model of the hip joint alters the initial surgical plan for FAIS correction.…”
mentioning
confidence: 99%